Regional Kitsch - Max Ryynänen (ESPES)
I hereby raise a new subdivision of kitsch to become an object of philosophical reflection. While a broad variety of objects is mentioned in studies on everyday kitsch – i.e. knickknacks, to here mark a difference towards bad ‘art’ called kitsch – there are no notes on regional kitsch per se. There is a difference between regional kitsch, anchored to regions and broader geographical wholes, and the type of ‘urban’ kitsch, which scholars have been discussing more, i.e. kitsch that presents kitschified versions of famous statues and architecture, objects that represent their cities (e.g. Michelangelo’s David represents Florence). While miniature David statues and Eiffel Towers are for tourists only, regional kitsch seems to have a more positive meaning for local inhabitants. Regional kitsch also focuses more on local culture through its everyday objects and atmosphere. Could it have a bigger role in building identity than what we have so far realized? The main aim of this article is to describe and present the phenomenon in the framework of kitsch research, and to provide a basis for further study of regional kitsch.